J curve: controversies - Castillo-Velarde, Edwin Rolando (2010)
Optimal control of hypertension requires knowledge of the pathophysiologic, clinical and therapeutic mechanisms, as well as support of recommendations on treatment goals, benefits and risks. Consequence of antihypertensive management is the presence of the J-curve that represents the presence of increased cardiovascular risk associated with diastolic pressure reduction. Although this curve has been debated for years, there are numerous reports about its existence and impact on morbidity and mortality, thereby providing an important reference when setting our goals of treatment.